2021
DOI: 10.3390/genes12111752
|View full text |Cite
|
Sign up to set email alerts
|

The Staphylococcus aureus CC398 Lineage: An Evolution Driven by the Acquisition of Prophages and Other Mobile Genetic Elements

Abstract: Among clinically relevant lineages of Staphylococcus aureus, the lineage or clonal complex 398 (CC398) is of particular interest. Strains from this lineage were only described as livestock colonizers until 2007. Progressively, cases of infection were reported in humans in contact with farm animals, and now, CC398 isolates are increasingly identified as the cause of severe infections even in patients without any contact with animals. These observations suggest that CC398 isolates have spread not only in the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 98 publications
2
11
0
Order By: Relevance
“…[ 133 ] reported that approximately 13% of LA-MRSA-positive patients who could not be typed by pulsed-field gel electrophoresis (PFGE) had an active infection compared with 42% of patients with LA-MRSA who could be typed by PFGE, which was less virulent than LA-MRSA. This is consistent with the fact that several virulence determinants have been identified among LA-MRSA CC398 [ 65 , 129 , 136 144 ]. However, it is necessary to continuously monitor the determinants and epidemiology of their virulence because several LA-MRSA CC398 isolates have been reported with important human virulence factors, including staphylococcal enterotoxins [ 65 , 139 ] and bicomponent Panton-Valentine leukocidin [ 129 , 137 , 138 , 141 , 142 ].…”
Section: Pig–pig Transmissionsupporting
confidence: 89%
See 2 more Smart Citations
“…[ 133 ] reported that approximately 13% of LA-MRSA-positive patients who could not be typed by pulsed-field gel electrophoresis (PFGE) had an active infection compared with 42% of patients with LA-MRSA who could be typed by PFGE, which was less virulent than LA-MRSA. This is consistent with the fact that several virulence determinants have been identified among LA-MRSA CC398 [ 65 , 129 , 136 144 ]. However, it is necessary to continuously monitor the determinants and epidemiology of their virulence because several LA-MRSA CC398 isolates have been reported with important human virulence factors, including staphylococcal enterotoxins [ 65 , 139 ] and bicomponent Panton-Valentine leukocidin [ 129 , 137 , 138 , 141 , 142 ].…”
Section: Pig–pig Transmissionsupporting
confidence: 89%
“…This is consistent with the fact that several virulence determinants have been identified among LA-MRSA CC398 [ 65 , 129 , 136 144 ]. However, it is necessary to continuously monitor the determinants and epidemiology of their virulence because several LA-MRSA CC398 isolates have been reported with important human virulence factors, including staphylococcal enterotoxins [ 65 , 139 ] and bicomponent Panton-Valentine leukocidin [ 129 , 137 , 138 , 141 , 142 ]. In addition, pig-associated LA-MRSA CC398 was linked with increased MRSA infections in Northern Europe [ 98 ].…”
Section: Pig–pig Transmissionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, none of the facilities included in the current study practises such intensive pig rearing. Markedly, MSSA cannot be overlooked as they form the reservoir from which MRSA arise [ 11 , 35 ]. The presence of antimicrobial resistance genes in the present study including tet M, tet K and tet L genes encoding for tetracycline resistance and erm B and erm C genes encoding resistance to erythromycin in some of the isolates indicate the need to closely monitor these strains as they may become a source of antimicrobial resistance given that some of these genes are harboured on plasmids which can be easily transferred between microorganisms [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…CC398 was originally described as a livestock-associated lineage, but it is also capable of causing human-to-human transmitted infections as reported from several countries. Phylogenetic evidence later revealed the existence of two distinct CC398 clades (livestock-and human-associated) differing in their repertoire of mobile genetic elements and virulence genes [61][62][63][64][65].…”
Section: Cc398mentioning
confidence: 99%